3x-2=-3x

Simple and best practice solution for 3x-2=-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2=-3x equation:


Simplifying
3x + -2 = -3x

Reorder the terms:
-2 + 3x = -3x

Solving
-2 + 3x = -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-2 + 3x + 3x = -3x + 3x

Combine like terms: 3x + 3x = 6x
-2 + 6x = -3x + 3x

Combine like terms: -3x + 3x = 0
-2 + 6x = 0

Add '2' to each side of the equation.
-2 + 2 + 6x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 6x = 0 + 2
6x = 0 + 2

Combine like terms: 0 + 2 = 2
6x = 2

Divide each side by '6'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 5x-15/2x-8 | | 4f-24+4f=-8-4 | | 8=d^2/3-1 | | 3x-4/10 | | x^2+64=x | | -6.4x=-4.8 | | 4c+8c=-54+3c | | -x+4x=-16+26x | | 24x+8=14x-6 | | cotx/sinx(secx-cosx)=1 | | 6=0.8*-4 | | 6(c-4)=48 | | 18-10x=-2 | | 8y=7x+8solvex | | 8-10x=-2 | | (2x^4-7x^3-5x+18)-(9x^3-7x+5)=0 | | 5x=2x+16 | | 8x-(5x-8)=3+2x | | 7(x+1)-4(x+3)=x-19 | | 5(k-3)-7=3k-(2k-1) | | (3x+2)=(2x-5) | | Log(3)*(5x-1)=3 | | 2-(11/n)=-(5/n^2) | | x-1/3=x-7/7 | | 2(3+6x)-5=7(x+8) | | 1050+5y=1050 | | R(x)=x^3+2 | | x^2+6x=28 | | 20b-3b-2=0 | | 3+ln(x+2)=6 | | p(x)=x^2-1 | | 12-h=22 |

Equations solver categories